Coprolite evidence for trophic reorganization of Early Triassic marine ecosystem after the Permian–Triassic mass extinction - Mingtao Yao; Zuoyu Sun; Yinuo Wang; Zhaoliang Ma; Torsten Scheyer; Cheng Ji; Shuang Liu; Jiandong Huang; Dayong Jiang (Global and Planetary Change, 2026)

Placodus (Placodontia, Sauropterygia) dentaries from Winterswijk, The Netherlands (middle Anisian) and Hünfeld, Hesse, Germany (late Anisian) with comments on ontogenetic changes - Nicole Klein; Tania Wintrich; Hans Hagdorn; Dave Spiller; Herman Winkelhorst; Gerard Goris; Torsten M. Scheyer (PalZ, 2022)
Two recently found dentaries from the Lower Muschelkalk of Winterswijk (The Netherlands) and from the Upper Muschelkalk of an outcrop in the vicinity of Hünfeld (Hesse, Germany) are studied and compared to lower jaws of placodonts. As a result, the here described specimens can be assigned to Placodus cf. gigas . However, this assignment should be regarded as preliminary due to the isolated nature of the material. More diagnostic material is necessary to validate this affiliation. A certain morphological variability in P. gigas dentaries that had been pointed out before is also obvious among the new material. Placodus gigas has a wide paleogeography and stratigraphic range and a revision of the material assigned to P. gigas with new methods is overdue but beyond the scope of the current paper. The dentary from Hünfeld is with about 4 cm preserved length the smallest so far known dentary of a Placodus . It provides interesting insights in morphological changes during ontogeny and reveals differences in trajectories when compared to dentaries of different ontogenetic stages of Cyamodus hildegardis.

Antiquity and fundamental processes of the antler cycle in Cervidae (Mammalia) - Gertrud E. Rössner; Loïc Costeur; Torsten M. Scheyer (The Science of Nature, 2021)
The origins of the regenerative nature of antlers, being branched and deciduous apophyseal appendages of frontal bones of cervid artiodactyls, have long been associated with permanent evolutionary precursors. In this study, we provide novel insight into growth modes of evolutionary early antlers. We analysed a total of 34 early antlers affiliated to ten species, including the oldest known, dating from the early and middle Miocene (approx. 18 to 12 million years old) of Europe. Our findings provide empirical data from the fossil record to demonstrate that growth patterns and a regular cycle of necrosis, abscission and regeneration are consistent with data from modern antlers. The diverse histological analyses indicate that primary processes and mechanisms of the modern antler cycle were not gradually acquired during evolution, but were fundamental from the earliest record of antler evolution and, hence, explanations why deer shed antlers have to be rooted in basic histogenetic mechanisms. The previous interpretation that proximal circular protuberances, burrs, are the categorical traits for ephemerality is refuted.

Placodont remains (Sauropsida, Sauropterygia) from the Triassic of Hungary (Transdanubian Range and Villány Mountains) - Kinga Gere; Torsten M. Scheyer; László Makádi; Attila Ősi (Palaeobiodiversity and Palaeoenvironments, 2020)
New placodont remains from the Triassic of Hungary are described here. They come from two different tectonic units: the Transdanubian Range Unit representing Alpine type sedimentary basins and the Villány-Bihar Unit that was part of the southern passive margin of the European Plate during the Triassic. The fossils came from four stratigraphic levels with the oldest specimen, a maxilla fragment found in the upper Anisian of Forrás Hill, near Felsőörs (Transdanubian Range). Based on dental morphology, the specimen is referred to here as Paraplacodus broilii . This site is similar in age to the Monte San Giorgio (Switzerland and Italy) locality. A Carnian occurrence of placodonts from this tectonical unit is a dentary fragment and two isolated teeth referred to here as Placochelys placodonta . The youngest specimen from this unit is a placochelyid tooth fragment from the Rhaetian of the Keszthely Mountains (Transdanubian Range). The richest assemblage of new placodont remains is from the Ladinian of the Villány Mountains, southern Hungary. Cranial elements are referred to here as Cyamodus sp. Teeth from this site are similar to that of Cyamodus sp. described from Slovenia, and both assemblages are among the last occurrences of the genus in the European Triassic. The Villány site is considered as a gap locality because of the rarity of Ladinian placodont occurrences in the German-Alpine sedimentary basins.

Microanatomy and life history in Palaeopleurosaurus (Rhynchocephalia: Pleurosauridae) from the Early Jurassic of Germany - Nicole Klein; Torsten M. Scheyer (The Science of Nature, 2017)

Aging the oldest turtles: the placodont affinities of Priscochelys hegnabrunnensis - Torsten M. Scheyer (The Science of Nature, 2008)

Two new species of the side necked turtle genus,Bairdemys (Pleurodira, Podocnemididae), from the Miocene of Venezuela - Eugene S. Gaffney; Torsten M. Scheyer; Kenneth G. Johnson; Jean Bocquentin; Orangel A. Aguilera (PalZ, 2008)